Branched hierarchical photoanode of anatase TiO2 nanotubes on rutile TiO2 nanorod arrays for efficient quantum dot-sensitized solar cells. Issue 8 (23rd January 2015) - Liu, Bingkun; Sun, Yanjun; Wang, Xuesong; Zhang, Lijing; Wang, Dejun; Fu, Zewen; Lin, Yanhong; Xie, Tengfeng
Abstract : The photoanode based on hierarchical TiO2 nanorod arrays exhibits a maximal power conversion efficiency of 1.04%, which is 2.7 times higher than that of a bare TiO2 nanorod photoanode. Abstract : We report novel hierarchical three-dimensional (3D) TiO2 nanotube-branched rutile TiO2 nanorod arrays (H-TiO2 NRAs) on FTO substrates that serve as model architecture for efficient quantum dot-sensitized solar cells (QDSCs). The newly designed H-TiO2 NRA photoanode offers a large surface area for high QD loading with high light scattering properties. In the meantime, the presence of anatase–rutile heterojunction at the interface helps the rutile nanorods to efficiently collect photo-injected electrons from the anatase nanotubes, reducing electron recombination with the electrolyte and QDs. As a result, the H-TiO2 NRA photoanode with a thickness of only 1 μm, exhibits a solar energy conversion efficiency of 1.04%, which is 2.7 times higher than that found in the pristine nanorod array-based QDSCs, demonstrating the synergistic effect of rutile nanorods and anatase nanotubes for photoelectrochemical solar energy conversion.